Integrating Sundanese Culture and Digital Technology: Designing an Ethnomathematics Based Worksheet Using GeoGebra for Conic Sections - Rani Sugiarni; Ari Septian; Sarah Inayah; Putri Salsabila; Novia Avivvah (Universitas Suryakancana, 2026)
Students struggle to determine simple equations when given the asymptotes and vertices or the equation of a hyperbola and the length of the major axis. This difficulty stems from the limited learning resources educators use when teaching conic sections. This study aims to develop GeoGebra-assisted worksheets that contextualize the concept of conic sections in a way that is valid and practical for high school students. This is a development study based on the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The test subjects in this study were 16 students from a private high school in Cianjur during the 2024–2025 academic year. The results of this study indicate that the GeoGebra-assisted worksheets for pupils, featuring contextual problems on the topic of conic sections, are valid and practical. The average expert validation score was 83.3%, meaning the average expert validation score falls within the “Highly valid” category and is suitable for testing. Meanwhile, the percentage of student responses to the GeoGebra-assisted worksheets developed was 75%, falling into the “Practical” category. This indicates that the developed material can be used as a teaching aid for senior secondary school students on the topic of conic sections. Developing mathematics teaching materials in the form of GeoGebra-assisted worksheets on the topic of conic sections for senior secondary school students, which have been tested for validity and practicality. The results of the development show that (1) the assessment of the GeoGebra-supported worksheets regarding the aspect of presentation suitability, using the Guttman scale, yielded an average of 83.3%, meeting the criterion of “highly valid.